Labor link and patient safety culture of a Huanuco health center - Borneo Cantalicio, Eler (2019)
Objective. To determine the relationship between the employment relationship and the culture of patient safety. Methods. A correlational design study was carried out with 51 family and community health workers from the Aparicio Pomares de Huánuco Health Center, during the 2018 period. A questionnaire on the culture of patient safety in primary care of the Medical Office Survey on Patient Safety was used. Culture (MOSPS) prepared by the Quality Agency of the National Health System of Spain and a scale of employment linkage of Schaufeli and Bakker. In the inferential analysis the Pearson r correlation test was used. Results. 62.7 % (32 health workers) had a very high employment relationship and 86.3 % (44 health workers) had a mid-level patient safety culture. On the other hand, the employment relationship is significantly related to the culture of patient safety, with p ≤ 0.008. And, also the safety culture of the patient is significantly related to the labor linkage in the dimension vigor (p ≤ 0.022), dedication (p ≤ 0.013) and absorption (p ≤ 0.012). Conclusions.The employment relationship is related to the safety culture of the patient in family and community health personnel of the Aparicio Pomares - Huánuco Health Center